Luteolin enhances erlotinib’s cell proliferation inhibitory and apoptotic effects in glioblastoma cell lines - Powe, Erika; Parschauer, Daniel; Istifan, Jessica; Lin, Stacy; Duan, Huanyun; Gryka, Rebecca; Jean-Louis, Denise; Tiwari, Amit K.; Amos, Samson (Frontiers in Pharmacology, 2022)
The epidermal growth factor (EGFR) receptor is frequently overexpressed in glioblastoma multiforme IV (GBM). Increased expression of EGFR leads to increased proliferation, decreased apoptosis, and increased resistance to chemotherapeutic agents. A small molecule called erlotinib inhibits EGFR receptors by binding to their adenosine triphosphate (ATP) binding sites. It is FDA approved to treat a variety of EGFR mediated cancers, Several clinical trials have explored the combination of erlotinib with other agents to treat glioblastoma since it is believed that erlotinib would benefit patients with GBM with EGFR mutations or expression. Luteolin, a natural flavonoid, inhibits cell growth and induces apoptosis in cancer cells. We investigated the combined effects of erlotinib and luteolin on proliferation and apoptosis on glioblastoma cell lines overexpressing EGFR or glioma cells expressing truncated EGFR (ΔEGFR). In a concentration-dependent fashion, the combination of luteolin and erlotinib reduced cell proliferation (p<0.05) and induced apoptosis by cleaving PARP and increasing caspase expression. In addition, the combination of luteolin and erlotinib reduced the phosphorylation of downstream EGFR cell signaling molecules such as Akt, NF kappa B, and STAT3 in a concentration-dependent manner. These findings suggest that combining luteolin with erlotinib offers a potential treatment strategy for glioblastoma multiforme IV.